La Nature est morte, vive la nature! - Callicott, J. Baird (The Hastings Center report, 1992)
The old, mechanistic idea of nature is dying. We are witnessing the shift to a new idea, in which nature is seen as an organic system that includes human beings as one of its components rather than as brutal and ultimately self-defeating conquistadores.